HUBUNGAN PENGETAHUAN DAN SIKAP IBU DENGAN PENANGANAN KEJANG DEMAM PADA BALITA SEBELUM DIRAWAT DI RUMAH SAKIT AHMAD YANI METRO - Wahid Tri Wahyudi; Rilyani Rilyani; Rahma Ellya (Universitas Malahayati Lampung, 2019)
ABSTRACT : THE CORRELATION OF KNOWLEDGE AND MOTHER’S ATTITUDE WITH THE HANDLING OF FEVER SEIZURESON TODDLER BEFORE BEING HOSPILALIZED AT HOSPITAL AHMAD YANI METRO Background : Infant Mortality Rate (AKABA) in Indonesia is still relatively high 40 per 1000 live births with a target of 32 per 1000 live births One cause of death in infants is caused by febrile seizures. From the research by various experts found that about 2.2% - 5% of children had experienced febrile seizures before they reached the age of 5 years. To prevent the impact of febrile seizures, the treatment of febrile seizures should be appropriate. Knowledge and awareness of mothers about febrile seizures is important to prevent the occurrence of febrile seizures in children.Purpose : The purpose of this study is to know the relationship of knowledge and attitude of the mother with the handling of febrile seizures in infants before being treated in RS Ahmad Yani Metro Year 2017.Method : This type of research is quantitative. The research design of analytic survey with cross sectional approach. The population in this study were all mothers who had a toddler with 3-year age febrile seizures at Ahmad Yani Metro Hospital in May, with a sample of 31 people. Stastistic test using chi-square test.Result : The result of bivariate analysis showed that there was a correlation between mother's knowledge with fever seizure handling in underfive before being treated in Ahmad Yani Metro Hospital 2017 (p-value = 0,003 and OR = 16,667) and there is relationship of mother attitude with febrile seizure handling before to be treated at Home Sick Ahmad Yani Metro Year 2017 (p-value = 0,002 OR = 19,250).Conclusion : Based on the results of research the researchers provide suggestions that need more improved knowledge and understanding of parents about handling febrile seizures at home in order not to cause a harmful impact toddlers. Keywords: Knowledge, Attitude, Seizures Fever